Makna kata Khalifah Dalam Qs. Al-Baqarah [2] : 30 ( Studi Komparasi Tafsir Al Manar Dan Jawahir) - Syahla Ghaziyah Salsabil; Imansyah Imansyah; Hanief Monady (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Humans, as khalifah (stewards) on Earth, have a great responsibility to lead and manage all aspects of life, whether in the family, society, or state, which will be accountable in the hereafter. This study examines the meaning of